Implications of Using Global Digital Elevation Models for Flood Risk Analysis in Cities. Issue 10 (2nd October 2020) - McClean, Fergus; Dawson, Richard; Kilsby, Chris
Abstract: As urban populations grow, it is increasingly important to accurately characterize flood risk in cities and built up areas. Global digital elevation models (GDEMs) have recently enabled flood risk analysis at broad scale and worldwide, but their accuracy and its impact on modeled flood risk in cities has not been fully investigated. We compare flood extents, hydrographs, depths, and impacts between hydrodynamic simulations, using five spaceborne GDEM products and an airborne LIDAR product. Benchmark observations of a historical flood event in Carlisle (UK) were used to assess the accuracy of each simulation. GDEM simulations are shown to perform significantly less accurately than the airborne LIDAR‐based simulations. No DEM outperforms the others across all metrics; the MERIT DEM is the best predictor of flood extent, but TanDEM‐X performs best for discharge. However, the impacts of flooding from GDEM simulations are consistently overestimated, 2 to 3 times higher than those from LIDAR simulations. Until a high resolution, accurate, global DEM is available, multiple products should be used concurrently to enable the full uncertainty range to be quantified and communicated, to ensure flood risk management decisions are not misinformed. Key Points: Flood models using five global DEMs are worse at predicting flood extents, hydrographs, and floodplain depths than a model using LIDAR Global DEM flood models consistently overestimate the impacts of flooding in a city by 2–3 times compared to a model using LIDAR No single global DEM performs best across all validation metrics, so multiple DEMs should be used to capture uncertainties in flood risk